1999
DOI: 10.1097/00005537-199909000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Telemedicine Applications for Otolaryngology

Abstract: These efforts performed in a stepwise approach will lead to an otolaryngology--head and neck surgery service that is on-line for the next millennium, with telemedicine advances normalized to the standard of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 1 publication
1
42
0
2
Order By: Relevance
“…The role of telemedicine in the delivery of otolaryngology services has been discussed widely [3][4][5][6], although large-scale multi-functional systems have to date received the most attention [7][8][9]. In most of these the role of telemedicine is discussed in general terms, together with a description of the equipment required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of telemedicine in the delivery of otolaryngology services has been discussed widely [3][4][5][6], although large-scale multi-functional systems have to date received the most attention [7][8][9]. In most of these the role of telemedicine is discussed in general terms, together with a description of the equipment required.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these the role of telemedicine is discussed in general terms, together with a description of the equipment required. However, some have gone into a some detail: Burgess [9] reported a good correlation between physical examination and video-otoscopy in a pilot study of 25 ears, Sclafini [5] found agreement of only 64% between a conventional assessment and a delayed assessment from stored images and data, and Pedersen [10] examined a number of patients using a video-endoscope to make assessment of various ENT disorders, and found that compressed images were equivalent in quality to standard endoscopic images.…”
Section: Introductionmentioning
confidence: 99%
“…Video otoscopy has found greater utilization in the last decade, primarily in telemedicine. Studies demonstrated that VO examination of the tympanic membrane is superior to otoscopy and as accurate and equally precise as the otomicroscopic examination when assessing for middle ear effusions [3,9,17,18,24,25]. Two to eight weeks after performing the in-person otoscopic examination, the same two validated otoscopists compared their previously reported otoscopic findings with their interpretations of middle ear effusion (MEE) from the VO-acquired videotapes done of the same ears [3,9].…”
Section: Clinical Appropriatenessmentioning
confidence: 99%
“…Tripler Army Medical Center in Hawaii has been especially prolific in producing telemedicine studies that deal with different treatment populations (Delaplain, Lindborg, Norton, & Hastings 1993;Cook, Hansen, Leckie, & Francoise 1995;Calcagni et al 1996;Norton et al 1996Norton et al , 1997Peters and Peters 1998;Birkmire-Peters, Peters, & Whitaker 1999;Burgess et al 1999;Garshnek and Hassell, 1999;and Hill, AUman, and Ditzler 2001.) The need for a framework within which to interpret and utilize the Navy's own ongoing assessment is readily apparent (Garshnek and Hassell 1999).…”
Section: Applicability Of Civilian Studiesmentioning
confidence: 99%